A laser-based multi-robot collision avoidance approach in unknown environments. (22nd February 2018) - Yu, Yingying; Wu, Zhiyong; Cao, Zhiqiang; Pang, Lei; Ren, Liang; Zhou, Chao
As a fundamental problem, collision avoidance for multiple robots still need further investigation, especially for many robots aggregating in a tight space. In this article, a laser-based collision avoidance approach is proposed in complex multi-robot environments. The laser data is analyzed and processed in terms of distance thresholding, safe passageway analysis, obstacles repulsion, goal position attraction, and inter-robot safety. Specifically, the safe passageway analysis is used to remove unsafe directions effectively, and inter-robot safety processing reduces the possibility of being selected for the directions affected by the neighboring robots. On this basis, an optimized decision is made to guarantee that the robots achieve collision-free motions even in crowded environments. The validity of the proposed approach is verified by simulations.